Effect of the processing parameters on the integrity of calcium phosphate coatings produced by RF-magnetron sputtering - Toque, Jay Arre; Abd Shukor, Mohd Hamdi; Ide-Ektessabi, A.; Sopyan, Iis (2009)
Calcium phosphate (CaP) compounds like hydroxyapatite and tricalcium phosphates are considered to be very important biomaterials. This study used RF-magnetron sputtering (RF-MS) to deposit CaP onto 316 LSS. Due to the complex nature of the effect of different sputtering parameters on the quality and integrity of the coatings, there is a need to further investigate those parameters collectively. An L(9)(3(4)) orthogonal array was employed to design the experiment that was used to investigate four important coating parameters which include RF-power, argon gas flow rate, deposition time and post-heat treatment conditions. The coating composition and structure were evaluated using XRD, EDX and FTIR. The mechanical property was measured in terms of the adhesion strength using a microscratch testing machine. The response graph of the results revealed that the interfacial strength of CaP was mainly influenced by the deposition power, while the coating thickness was predominantly affected by the argon gas flow rate. High adhesion strength was achieved when the coatings have at least 2 mu m thickness and deposited at a working pressure of 12 m Torr. A NOVA on the control factors helped rank the parameters accordingly in order of importance. Based on the response of the control factors, it was found that optimum adhesion strength could be achieved by depositing the coatings using the following parameters: 10 sccm of argon gas flow rate; 150 W of RF power; and 16 h of deposition.